Konsep Diri Remaja Jawa saat Bersama Teman - - Sartana; Avin Fadilla Helmi (Jurnal Psikologi, 2014)
The aim of the study was to formulate a theory about Javanese adolescent self-concept in relation with friends. The subjects of this research were three Javanese adolescents, two girls and one boy. Data were collected through in-depth interviews and observation and were analyzed with the so-called grounded theory approach. The results of this study indicated that Javanese adolescents interprets himself as plural selves, hierarchical interdependent and altered. Individuals have a lot of selves that represent their relationships with others. The selves are composed with each other in a hierarchical relationship. In a particular time, an individual activates one only of their selves. The self-activation process goes with the principle of "if ..., then ...". After recognizing their friends and situations, individuals will compare and evaluate themselves then choosing and activating one particular self to adjust with a particular friend and situation. When Javanese adolescents are with their friends, they do not think much about physical aspect, they become themselves and feel equal, accepted, understood and trusted as a good person. Such self-viewing makes an individual tend to go through positive feelings and comfort being around friends. Keywords: self-concept, self-adjustment, adolescents, Javanese, friends